Small instream infrastructure: Comparative methods and evidence of environmental and ecological responses - Januchowski‐Hartley, Stephanie R.; Mantel, Sukhmani; Celi, Jorge; Hermoso, Virgilio; White, James C.; Blankenship, Scott; Olden, Julian D. (Wiley, 2020)
1. Around the globe, instream infrastructures such as dams, weirs, and culverts associated with roads are wide‐spread and continue to be constructed. There is limited documentation of smaller infrastructure because of mixed regulation and laws related to instream construction, as well as difficulty in documentation because of their size and frequency in waterscapes. 2. We reviewed evidence of different methods used to quantify environmental and ecological responses (positive, negative, or neutral) to dams, weirs, and culverts. 3. Most studies (78% of 87) in our review evaluated dams or weirs, and more than half evaluated environmental or ecological responses at more than one of these structures. More than half of the studies used spatial (disturbed–undisturbed in the same or a different catchment) rather than temporal (before–after construction or before–after destruction) comparative methods. Evaluations also tended to focus on ecological variables, most specifically on fish community responses (just over a quarter) to infrastructure. 4. More than half (58%) of the evaluations at dams, weirs, or culverts reported negative environmental or ecological responses. Discrepancies in responses recorded for different infrastructure types could be partially explained by the focus on ecological responses in reviewed studies and related metrics used for evaluations (e.g. biotic groups, richness, and abundance), the imbalance of studies at different infrastructure types, and discrepancies in spatial and temporal scales of evaluations compared to those at which the variables respond to infrastructure. 5. Despite the abundance of road culverts greatly exceeding the number of small or large dams worldwide, they were evaluated in only 22% of studies that we reviewed. Our findings underscore the need for studies to not only better understand local but also cumulative impacts of these smaller infrastructure, as these could be greater than those caused by large infrastructure depending on their location, density, and type, among other factors. Such studies are needed to inform infrastructure planning and watershed management.
Keywords: dams; evaluation; freshwater ecosystems; rivers; roads; weirs